DEVELOPMENT OF EDUCAPLAY-BASED LEARNING MEDIA IN THE ELEMENTS OF HUMAN RESOURCE MANAGEMENT CLASS XI OFFICE MANAGEMENT OF VOCATIONAL SCHOOL - Fitriyana, Delisa Alif; Rosy , Brillian (Universitas Negeri Surabaya, 2024)
Phenomenon/Issue: There is a need to develop engaging and effective learning media for teaching Human Resource Management in class XI Office Management at Vocational School 4 Surabaya. Purpose: This study aims to determine the development process, feasibility, student responses, and effectiveness of Educaplay-based learning media in supporting Human Resource Management learning. Novelty: The study introduces the use of Educaplay-based learning media, an innovative approach combining interactive tools tailored to enhance student learning experiences in vocational education settings. Research Methods: The study employs the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Research instruments consist of validation sheets (from material and media experts), student response questionnaires, and pre-test and post-test sheets to measure effectiveness. Results: The validation results show that Educaplay-based learning media is highly feasible, receiving scores of 91% from material experts, 96.66% from media experts, and 92.33% from student responses. The effectiveness test using the n-gain score yielded 70%, categorized as